Teknik Pemrosesan Gambar Digital pada Hasil Pengelasan TIG Aluminum Paduan untuk Aplikasi Pengukuran Lebar Manik Las - Azwar Amat, Mohammad; Luthfi, Muhammad (Politeknik Negeri Indramayu, 2023)
ABSTRACT – The process of edge detection on aluminum 1100 material as a result of welding tungstent inert gas (TIG) has been successfully developed, difficulties in the edge detection process due to the large number of impurities in the form of vertical streaks on the weld metal can be overcome using several methods. Of the many methods used, double thresholding and hysterisis have the most important role and contribution in the process of cleaning impurities. The hough transform process requires setting the number of meeting lines to get two lines with rho = (229, 146) and theta = (1.582496, 1.553343). Method 4 is the shortest method of pre-processing until line detection, namely GS > Gauss > Sobel > DT > Hys > HT. In further development, the development of an interface that makes it easy to vary the threshold value and the number of meeting lines, then the pixel/mm or pixel/cm scale calibration process needs to be carried out.